The Influence of CSR, the Size of the Board of Commissioners and Leverage on Profitability of Manufacturing Companies Listed in BEI - Thomas Sumarsan Goh; Henry Henry; Erika Erika (Budapest International Research and Critics University, 2021)
This research aims to know the impact of CSR, number of commissioners committee and leverage on profitability at manufacturing companies at Indonesian Stock Exchange. This study is quantitative descriptive. The data collection is from taking manufacturing companies’ financial statements that are listed at Indonesian Stock Exchange, according to the number of samples, selecting from purposive sampling. Data analysis method is multiple regression method at 5% of significant. The result of the study is the coefficient determination is 20.6%, means that the impact of independent variables is 20.6%, and the remaining is affected by other variables. The result of the study shows that leverage has impact on ROA, partially, and CSR and number of commissioner have no impact on ROA; however, simultaneously, CSR, number of commisioners and leverage has impacted significantly on ROA